Legal Analysis Of Handling The Criminal Acts Of Circulation And Use Of Counterfeit Rupiah Curriculum : Research Study At The Kepri Regional Police - Panca Gunawan Harefa; Fadlan Fadlan; Parameshwara Parameshwara; Soerya Respationo; Erniyanti Erniyanti (FKIP, Universitas Palangka Raya, 2024)
This thesis discusses the handling of criminal acts of using and circulating counterfeit rupiah banknotes, with a focus on law enforcement efforts by the Riau Islands Regional Police. This research is motivated by the increasing cases of counterfeit rupiah banknotes in the Riau Islands which cause significant losses to the community and threaten regional economic stability. The main objective of this study is to analyze the effectiveness of law enforcement carried out by local police, as well as to identify and overcome obstacles faced in the process. The research method used is a qualitative approach, with data collection techniques through in-depth interviews, participatory observations, and documentation studies. The sample of this study consisted of police officers, legal experts, and victims of counterfeiting money. Data analysis was carried out using content analysis techniques to interpret the collected data, based on the framework of the theory of legal certainty from Sudikno Mertokusumo, the theory of legal systems from Lawrence M. Friedman, and the theory of Crime Prevention Through Environmental Design (CPTED). The results show that law enforcement against rupiah counterfeiting in the Riau Islands faces several major obstacles, including limited resources, inter-agency coordination problems, and a lack of adequate training for law enforcement officers.The suggestions resulting from this study include increasing the allocation of resources, both in the form of equipment and training for officers, as well as strengthening cooperation between institutions involved in law enforcement, to increase effectiveness in identifying, preventing, and cracking down on the crime of using and circulating counterfeit money.